Total antioxidant capacity and superoxide dismutase activity levels in serum and gingival crevicular fluid in post-menopausal women with chronic periodontitis - Esra BaltaciogË˜ lu (journal of clinical periodontology, 2006)
Objectives: Menopause has been linked with oxidative stress and decreased antioxidant (AO) defence. A connection has been established between menopause and certain periodontal conditions. The objective of this study is to compare serum and gingival crevicular fluid (GCF) total antioxidant capacity (TAOC) and superoxide dismutase (SOD) concentrations in post-menopausal patients with chronic periodontitis (PMCP) with those of pre-menopausal chronic periodontitis patients (CP). Material and Methods: Thirty-two PMCP patients, 31 CP patients, 25 postmenopausal periodontally healthy controls (PMPH) and 26 pre-menopausal controls (PH) were studied. After clinical measurements and samplings, serum and GCF TAOC and SOD concentrations were established in turn using an automated TAOC assay and spectrophotometric end point measurement. The results were analysed statistically. Results: Serum and GCF TAOC and SOD concentrations were significantly lower in menopause and periodontitis (po0.05). The lowest values were in the PMCP group, whereas the highest values were in the PH group. While the effect of menopause was more evident in serum antioxidant analysis, the effect of periodontitis was observed to be more apparent in GCF. Conclusions: A decrease in systemic and local AO defence was observed owing to both menopause and periodontitis. The lowest AO values in the PMCP group suggest that menopause may be a risk factor for periodontitis.